Pengolahan Limbah Domestik PT X Dengan Unit Anaerobic Buffle Reaktor - Namira Namira; Tuhu Agung Rachmanto (Pusat Riset dan Inovasi Nasional, 2024)
Domestic waste produced by one of the chicken cutting industries, PT X, in the Jombang region, East Java, has not been properly treated. Domestic waste, commonly known as greywater, is wastewater originating from kitchen activities, toilets, sinks, and so on, carried out by the workers. If this wastewater is directly discharged into the environment without prior treatment, it can cause pollution and have adverse effects on aquatic life. One of the efforts to manage PT X's domestic waste is by using the Anaerobic Baffle Reactor (ABR) unit. The selection of the ABR unit is based on the treatment system at PT X's wastewater treatment plant (IPAL). In this IPAL, there is a sedimentation process and degradation of organic material by anaerobic bacteria, which can minimize the land use for domestic wastewater treatment. The aim of this research is to determine the efficiency in reducing parameters present in PT X's domestic wastewater, namely COD, BOD, and TSS. This study is expected to provide an alternative for treating domestic waste at PT X so that the discharged waste does not pollute the surrounding factory environment.